Financial literacy of selected college students in Quezon City - Nava, Kathleen Rose A.; Dare, Evangeline M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
This is a descriptive study of the level of financial literacy among undergraduate B.S. Home Economics students from the University of the Philippines, Diliman, Quezon City. The study defined financial literacy in terms of applications and knowledge of basic financial concepts such as price increase/decrease in pesos and in percent, purchasing power, appreciation and depreciation of currencies, simple and compound interest and present value of future money. The study covered the differences in the level of financial literacy of respondents using these variables: gender, year-level, socio-economic status and background on money management or personal finance. It also aimed to find out the respondents‟ sources of financial knowledge, financial management practices, priorities in budgeting and spending and their interest in increasing financial knowledge. Purposive sampling was used to identify respondents. Descriptive statistics, frequency, percentage distribution, and tests such as T-test and One-Way ANOVA test were used to analyze the gathered data. Findings confirmed that more than half of the respondents (51.1 percent) have a low level of financial literacy; the rest (46.9 percent) have a medium level. Based on statistical evidences, being financially literate is highly independent of gender, socio-economic status, and background on money management or personal finance; but it is dependent on the year level of the respondent.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Financial literacy -- Philippines